SWOT ANALYSIS AS THE BASIS FOR MARKETING STRATEGY OF PT AMERTA INDAH OTSUKA - Eka Mayasari; Rubingatun Rubingatun; Nuryadi Nuryadi (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2026)
The increasing competition in the beverage industry requires companies to implement adaptive marketing strategies to maintain their competitive advantage. This study aims to analyze the implementation of the marketing strategy of PT Amerta Indah Otsuka using the Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis. This research employed a descriptive qualitative method, with data collected through observation, interviews, and documentation. Data were analyzed using the SWOT matrix to identify the company's internal and external factors. The findings indicate that PT Amerta Indah Otsuka's key strengths include strong brand equity, consistent product quality, continuous product innovation, and an extensive distribution network. The company also benefits from growing consumer awareness of healthy lifestyles and the expansion of digital marketing opportunities, while facing challenges from intense market competition and changing consumer preferences. Based on the SWOT analysis, the company is positioned to pursue a growth strategy by strengthening product innovation, optimizing digital marketing, and expanding its distribution network. These findings suggest that SWOT analysis serves as an effective strategic tool for developing competitive and sustainable marketing strategies.